Religious Coping pada Penghafal Al-Qur’an dalam Menghadapi Fase Krisis Seperempat Baya - Aulia Muna Majidah; Sri Lestari (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
This research aims to obtain an overview of the strategies used by memorizers of the Quran in facing the quarter-life crisis phase. The quarter-life crisis is an emotional crisis related to doubt or anxiety about the future which is usually experienced by individuals aged 18-25 years. The research used qualitative phenomenological methods with thematic analysis. The participants were four students selected through purposive sampling. The results show that the area where the quarter-life crisis is most experienced is in the area of work. The causal factor is family life. The impacts can be negative, such as overthinking and anxiety; or positive, such as being able to learn lessons and be more aware of future challenges. Strategies for overcoming crises include preparing themselves by studying, reading the Quran, and believing that religion can help them face their life problems. The implications of this research emphasize that getting closer to Allah Swt. through the activity of reading and memorizing the Quran can strengthen individuals to face a quarter-life crisis.